Internalisasi akhlak sebagai solusi atas penyimpangan generasi Kpopers dalam perspektif al-Qur’an - Pertiwi, Safira Ramadhani (Maliki Interdisciplinary Journal, 2023)
The rise of k-pop culture in Indonesia is a significant problem. K-pop is one of the artist idoized by the Indonesian People. Regardless of age, from children to adults become a fan of Korean artist. The lack of filtering of the incoming culture has led to the rise of deviation in society. From fanaticism, hedonism, to consumptiveness become the daily food of k-popers. The k-popers morals have become something that deviates from religious values, especially Islam, which is the majority religion in Indonesia. The behaviour of k-popers is more concerned with wants than needs which are very excessivw or israf without seeing whether or not the benefits of the intem are important.